The quests for glory - Chainani, Soman (School for Good and Evil, 2017)
"The students at the School for Good and Evil thought they had found their final Ever After when they vanquished the malevolent School Master. Now on their required fourth year quests, the students face obstacles both dangerous and unpredictable, and the stakes are high: success brings eternal adoration, and failure means obscurity forever. For their quests, Agatha and Tedros are trying to return Camelot to its former splendor as queen and king. For her quest, Dean Sophie seeks to mold Evil in her own image. But soon they all feel themselves growing more isolated and alone. When their classmates' quests plunge into chaos, however, someone must lead the charge to save them. If Good and Evil can't find a way to work together, neither side will survive"--Publisher's website.